2019
DOI: 10.2217/rme-2018-0133
|View full text |Cite
|
Sign up to set email alerts
|

Early Natural History of Neotissue Formation in Tissue-Engineered Vascular Grafts in a Murine Model

Abstract: To characterize early events in neotissue formation during the first 2 weeks after vascular scaffold implantation. Materials & methods: Biodegradable polymeric scaffolds were implanted as abdominal inferior vena cava interposition grafts in wild-type mice. Results: All scaffolds explanted at day 1 contained a platelet-rich mural thrombus. Within the first few days, the majority of cell infiltration appeared to be from myeloid cells at the peritoneal surface with modest infiltration along the lumen. Host reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…Our prior work characterized proliferating cells within TEVGs and found two predominate populations, F4/80+ (macrophage specific) staining and COL1A1+ staining cells in accordance with classically described foreign body response. [ 4,35 ] Presently, we found that the degree of macrophage infiltration and ratio of PCNA+ cells in the graft at 14 d was independent of both seeding scheme and recipient genotype. This is in contrast to previous work showing TEVGs seeded with BM‐MNCs have decreased macrophage infiltration compared to unseeded TEVGs at 14 d postimplantation.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Our prior work characterized proliferating cells within TEVGs and found two predominate populations, F4/80+ (macrophage specific) staining and COL1A1+ staining cells in accordance with classically described foreign body response. [ 4,35 ] Presently, we found that the degree of macrophage infiltration and ratio of PCNA+ cells in the graft at 14 d was independent of both seeding scheme and recipient genotype. This is in contrast to previous work showing TEVGs seeded with BM‐MNCs have decreased macrophage infiltration compared to unseeded TEVGs at 14 d postimplantation.…”
Section: Discussionmentioning
confidence: 74%
“…Both F4/80 and CD68 suffer from off‐target staining of leukocytes other than macrophages in addition to expression intensity differences in TEVGs at different time points. [ 4,36–38 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also observed contractile cells within the neointima of tissue engineered vessels. [43] Statistical regression analysis comparing the implanted scaffold parameters to the explanted neovessel characteristics demonstrated that the PGS coating decreased inflammation and increased collagen accumulation. The lower inflammation and macrophage density seen at explant (12 weeks), in comparison to other polymer-based vascular grafts at similar time, [22,23,44] likely reflected the near complete degradation of polymer by 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Reinhardt and colleagues developed lyophilized vascular scaffolds from poly (glycolic acid) (PGA) and polycaprolactone-co-lactide (PCLA). Firstly, a solution of these polymers was inserted in a cylinder which was snap-frozen at −20°C for 20 min and then lyophilized for 24 h. The authors obtained highly porous scaffolds with an inner diameter of 0.91 mm and wall thickness of 300 μm ( 71 ). Wang and colleagues developed poly-L-lactic acid (PLLA), poly(L-lactide- co -caprolactone) (PLCL) and poly(lactic- co -glycolic acid) (PLGA) scaffolds by dual phase separation technique and lyophilization.…”
Section: Vte Techniquesmentioning
confidence: 99%